Rhabdomyolysis and coronavirus disease‐2019 in children: A case report and review of the literature. Issue 2 (1st April 2022) - Kontou, Maria; Kakleas, Konstantinos; Kimioni, Vaso; Georgiadi, Dimitra; Spoulou, Vasiliki; Michos, Athanasios
ABSTRACT: Introduction: Coronavirus disease‐2019 (COVID‐19) presents with a variety of symptoms, but rhabdomyolysis has rarely been reported in children. Case presentation: We report a 10‐year‐old girl who presented with fever, myalgia, and limping. The patient was tested positive for severe acute respiratory syndrome coronavirus‐2. On admission, creatine kinase (CK) level was 13 147 units per liter and the patient was diagnosed with rhabdomyolysis. She was treated with intravenous fluids, which resulted in CK levels decrease. There are currently seven case reports of children with rhabdomyolysis associated with acute COVID‐19 infection and two reports with the multisystemic inflammatory syndrome. Conclusion: Children presenting with muscle pain and weakness in the acute phase or following COVID‐19 infection, should alert physicians of the possibility of rhabdomyolysis. Abstract : LEARNING POINTS Rabdomyolysis could be the clinical manifestation of acute SARS‐COV‐2 infection or multisystem inflammatory syndrome (MIS‐C). Clinical improvement of rhabdomyolysis after IVIG suggests an immune‐mediated mechanism. There is no clear evidence that bicarbonate therapy is more effective than saline diuresis in preventing acute kidney injury.